2017
DOI: 10.1002/pmic.201700145
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Proteome Patterns of Egg Albumen from Domestic Chicken, Duck, Goose, Turkey, Quail and Pigeon

Abstract: To uncover a diversity of genetic and biological unknowns, a comprehensive and comparative proteomic analysis is performed on egg albumen of domestic chicken, duck, goose, turkey, quail, and pigeon with tandem mass tags quantification technology. In this study, a total of 148, 138, 150, 162, 183, and 179 proteins are identified in egg albumen of the above six species, respectively. Venn plots, PCA, and cluster analysis all reveal the highest similarity of protein composition between duck and goose (≈75%). Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 63 publications
0
35
0
Order By: Relevance
“…The rs14491030 located in the missense of gene NCAPG (non-SMC condensin I complex, subunit G). The gene has a pleiotropy function on many traits, like residual feed intake in bovines (Widmann et al, 2015), withers height in horses (Tetens et al, 2013), and body weight in chickens (Setoguchi et al, 2009). The results of our population study revealed that NCAPG may affect egg weight because albumen is the major contributor to egg weight (Silversides and Budgell, 2004).…”
Section: Discussionmentioning
confidence: 74%
“…The rs14491030 located in the missense of gene NCAPG (non-SMC condensin I complex, subunit G). The gene has a pleiotropy function on many traits, like residual feed intake in bovines (Widmann et al, 2015), withers height in horses (Tetens et al, 2013), and body weight in chickens (Setoguchi et al, 2009). The results of our population study revealed that NCAPG may affect egg weight because albumen is the major contributor to egg weight (Silversides and Budgell, 2004).…”
Section: Discussionmentioning
confidence: 74%
“…For manipulations with AMPs, commercially available lysozyme (L6876, Sigma-Aldrich) and ovotransferrin (C0755, Sigma-Aldrich) purified from hen egg whites were used. Although several types of lysozyme exist, variously distributed across egg whites of avian species (Thammasiririak et al, 2007;Callewaert and Michiels, 2010;Sun et al, 2017), all lysozyme types exhibit similarity in their three-dimensional structure (Callewaert and Michiels, 2010), have nearly identical pH optima for their antimicrobial activity (Thammasiririak et al, 2007) and comprise the majority of hydrolytic enzymes in avian egg whites (Sun et al, 2017). We can therefore exclude potential bias resulting from using purified chicken lysozyme and ovotransferrin in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a second line of defence in the form of egg white AMPs exists, protecting the developing embryo against invading microbes. Recent studies have identified more than 180 different egg white proteins in chicken eggs (Mann and Mann, 2011;Sun et al, 2017). Of these, lysozyme and ovotransferrin are the most abundant (Burley and Vadehra, 1989), having physiological (Giansanti et al, 2012;Javurkova et al, 2015; Krkavcová et al, 2018) and strong antimicrobial potential (Baron and Jan, 2011;Wellman-Labadie et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Pigeon eggs are praised as “animal ginseng” due to their many ingredients with high nutritional value such as protein, lecithin, vitamins and iron. They are a safe and healthy food source and can be a medicated diet for all ages [1,2]. With the improvement in living standards for humans and the optimization of the consumption structure, pigeon eggs are no longer used just for feasts but are also gradually being used for daily consumption.…”
Section: Introductionmentioning
confidence: 99%